Does Internalizing Society and Media Messages Cause Body Dissatisfaction, in Turn Causing Disordered Eating?. Issue 2 (3rd March 2016) - Dye, Heather
Abstract : The purpose of this study was to examine the predictive influence that internalization of society and media messages has on body dissatisfaction, as well as the prediction influence that body dissatisfaction has on disordered eating behaviors, such as preoccupation with weight, dieting, and eating restraint. A total of 324 participants completed the demographic questionnaire, the Multidimensional Body Self Relations Questionnaire (Cash, 2001 ), the Sociocultural Attitudes Towards Appearance Questionnaire (Heinberg, Thompson, & Stormer, 1995 ) for women, and the Sociocultural Attitudes Towards Appearance Questionnaire-Revised-Male-Version (Cusumano & Thompson, 1997 ) for men, and the locus of control (Rotter, 1966 ). The results of this study found that high internalization leads to body dissatisfaction, in turn, leading to disordered eating behaviors, such as preoccupation with weight, dieting, and eating restraint. This study proposes the implementation of media literacy and education programs that teach college women and men, girls and boys, to think more critically about the media.